A Chemical and Morphological study of some Crataegus L. spieces in the Syrian Coast - غانم بتول; محمد احمد ناصر; ريم سلامة (Latakia University Journal -Medical Sciences Series, 2024)
This study was conducted on a medicinal plant known as the "food of the heart" from the Rosaceae family، specifically hawthorn (Crataegus L.)، which is widely distributed along the Syrian coast. Plant samples of various species (flowers، leaves، fruits) from the genus Crataegus L. were collected from different areas along the Syrian coast، specifically in Tartus Governorate، during the year 2022. These samples differed morphologically at the time of collection. The study involved identifying the collected species by comparing them with specialized botanical floras and consulting experts. Additionally، total phenolic compounds and flavonoid compounds were extracted from the flowers، leaves، and fruits in their dried state and quantitatively assessed using a spectrophotometer according to the Folin-Ciocalteu method and the aluminum chloride colorimetric method، which are standard procedures for total phenolics and flavonoids، respectively. The results indicated the presence of two main species of the genus Crataegus in the studied area: Crataegus monogyna Jacq and Crataegus azarolus L. It was found that the species Crataegus azarolus L. with yellow fruits (Mouterde) is the same as Crataegus aronia L. (Zohary)، which has been classified as a variety in modern taxonomy (KEW)، specifically Azarolus var. Aronia Crataegus. The total phenolic content in the flower extracts was found to be 22.76 and 17.34 mg Gallic acid/g dry weight (d.w)، in the leaf extracts 8.198 and 4.425 mg Gallic acid/g d.w، and in the fruit extracts 0.412 and 1.81 mg Gallic acid/g d.w for the species Crataegus monogyna Jacq and Crataegus azarolus L.، respectively. Additionally، the flavonoid content in the flower extracts was 0.46 and 1.047 mg Rutin equivalents (R.E)/g d.w، in the leaf extracts 2.37 and 1.65 mg R.E/g d.w، and in the fruit extracts 0.099 and 0.096 mg R.E/g d.w for the species Crataegus monogyna Jacq and Crataegus azarolus L.، respectively.